Childhood chronic pancreatitis - Basnet, S; Sharma, AK (Journal of Institute of Medicine Nepal, 2010)
Chronic pancreatitis is one of the rare cause of abdominal pain in children. We report a seven year old boy with recurrent episodes of epigastric pain for one year which was ultimately diagnosed as chronic idiopathic pancreatitis, we discuss the evaluation and treatment of chronic pancreatitis. DOI: http://dx.doi.org/10.3126/joim.v32i1.4000 Journal of Institute of Medicine, April, 2010; 32:1 pp.37-39